The association patterns between socio-demographic, clinical and treatment-related characteristics in multidrug-resistant tuberculosis patients in Malaysia - Fahrurazi, Fairul Ezwan (2018)
Introduction: The emergence and increasing number of multidrug-resistant tuberculosis (MDR-TB) worldwide have posed new threats to public health locally and globally. There are a number of important patient’s characteristic for MDR-TB. However, there are no studies published about association between the characteristics of MDR-TB patient in Malaysia. Objective: The objective of this study was to describe the socio-demographic, clinical and treatment related characteristics of MDR-TB patients in Malaysia and to determine the association patterns between the characteristics of MDR-TB patients in Malaysia Methods: Analysis of secondary data from a cross-sectional design study on registry of Tuberculosis Information System (TBIS) of Ministry of Health Malaysia. Socio-demographic, clinical and treatment related characteristics of MDR-TB patient were extracted from the databases. Log-linear regression was used to identify association patterns between the characteristics with odd ratios and 95% confidence interval. Results: There were 395 cases of MDR-TB reported across Malaysia from 2012 to 2016. Odds of immigrant were 77% lower in old age than young age (OR = 0.23, 95% CI: 0.11, 0.43). Odds of male gender were 2.37 times in old age group than young age group. (OR = 2.37, 95% CI: 1.45, 3.95). Odds of male gender were 5.22 times in HIV positive status group than negative HIV status (OR = 5.22, 95% CI: 1.48, 33.12). Odds of previous TB treatment were 78% higher in male than female (OR = 1.78, 95% CI: 1.13, 2.82) and 52% lower in positive sputum status than negative sputum status (OR = 0.48, 95% CI: 0.30, 0.78).Conclusion: Log-linear analysis revealed that there are association between age category and immigrant status, age category and gender, gender and HIV, gender and history of previous TB treatment, and history of previous TB treatment and sputum status.